Glycogen storage disease type 0 due to a novel frameshift mutation in glycogen synthase 2 (GYS2) gene in a child presenting with fasting hypoglycemia and postprandial hyperglycemia - Hacıhamdioğlu, Bülent; Özgürhan, Gamze; Çaran, Bahar; Meydan-Aksanlı, Evrim; Keskin, Ece (The Turkish Journal of Pediatrics, 2018)
Glycogen storage disease type 0 (GSD0) has been considered a rare disorder, it is characterized with ketotic hypoglycemia after prolonged fasting and postprandial hyperglycemia. Herein, we report a novel mutation in the glycogen synthase 2 gene in a Turkish child, as well as her clinical characteristics and 12-month follow-up. We evaluated a 5-year-old girl for asymptomatic fasting ketotic hypoglycemia with postprandial hyperglycemia diagnosed with glycogen storage disease type 0. We identified a novel frameshift mutation, c.1081delA (p.Thr361Glnfs*2) in exon 8 on glycogen synthase 2 gene. Children with GSD0 may have a mild phenotype and GSD0 may be underdiagnosed due to subclinical or asymptomatic hypoglycemia. The diagnosis of GSD0 should be considered in a child with ketotic fasting hypoglycemia with postprandial hyperglycemia but without hepatomegaly.
Keywords: glycogen storage disease type 0; glycogen synthase 2 gene; ketotic hypoglycemia